(untitled) (Proceedings of the International Conference on Public Health, 2022)
Pregnant women are classified as one of the groups who have a high risk of flu complications. the flu vaccination uptake in pregnant women in the United Kingdom is still low and a slight decrease reported which was from 45.2% in 2018-2019 to 43.7% in 2019-2020. This systematic review aims to explore the factors which influence pregnant women undertaking or refusing flu vaccination. Six electronic databases were included, such as MEDLINE, CINAHL, PsycInfo, EMBASE, PubMed, Scopus, and grey literature. This systematic review selected full texts English language and the studies from 2009 to 2019. Data were assessed using CASP checklists, extracted, and synthesised. The results of the review are the views of pregnant women from the multicultural community from many different countries aged 18-48 based on 4 included studies. The themes were grouped using thematic analysis and produced 7 new analytic themes. The barriers are acceptability; service provision; lack of information; communication and interaction. The facilitators are benefits for the babies and the vulnerable environment. One theme that acted as a barrier and facilitator is the influence of others, such as family, friends and community. Reducing the barriers will lead to an increasing in flu vaccination uptake in pregnant women, therefore, the improvement of health care services and providing greater information regarding flu vaccination are needed. The facilitators should be used as ways to inform pregnant women about the benefits and risks.